2012
DOI: 10.1021/je201149u
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Thiotriazinone in Binary Solvent Mixtures of Water + Methanol and Water + Ethanol from (283 to 330) K

Abstract: The solubility of thiotriazinone in water, methanol, ethanol, water + methanol, and water + ethanol has been measured under temperatures ranging from (283 to 330) K with a laser technique. The results of these measurements were correlated with semiempirical equations. The calculated results have showed fine representativity of experimental data. The stepwise regression method was used to simplify the modified Jouyban–Acree equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 10 publications
0
40
0
Order By: Relevance
“…It has been demonstrated that the modified van't Hoff equation (Eq. (5)) can be successfully applied in the correlation of the solubility in the pure solvent [26,27]. For the system in this work, the solubility of creatine monohydrate in water and ethanol is presented as Eqs.…”
Section: Correlation Of Creatine Monohydrate Solubilitymentioning
confidence: 99%
“…It has been demonstrated that the modified van't Hoff equation (Eq. (5)) can be successfully applied in the correlation of the solubility in the pure solvent [26,27]. For the system in this work, the solubility of creatine monohydrate in water and ethanol is presented as Eqs.…”
Section: Correlation Of Creatine Monohydrate Solubilitymentioning
confidence: 99%
“…11 Solubility data at different temperatures could be correlated by the van't Hoff equation 12,13 = + x A B T ln T sat (2) and for a nonlinear relationship, a three parameter equation could also be used, 12…”
Section: Introductionmentioning
confidence: 99%
“…In order to consider both temperature and solvent composition of the binary solvent mixtures, the Jouyban‐Acree model was modified in conjunction with the modified Apelblat equation : true right1 left ln xnormalA = xnormalB 0 ( a2 + b2 T + c2 lnT)+ xnormalC 0 ( a3 + b3 T + c3 lnT) right1 left + xnormalB 0 xnormalC 0 T normali=0 2 Jnormali ( xnormalB 0 - xnormalC 0 )normali …”
Section: Resultsmentioning
confidence: 99%
“…After replacing x C 0 by (1 – x B 0 ) and introducing a constant term, Eq. can be rearranged to : true right1 left ln xnormalA = B1 + B2 T + B3 lnT+ B4 xnormalB 0 right1 left + B5 xnormalB 0 T + B6 ( xnormalB 0 )2 T + B7 ( xnormalB 0 )3 T right1 left + B8 ( xnormalB 0 )4 T + B9 xnormalB 0 lnT …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation